2021
DOI: 10.21608/ejhc.2021.138121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Intervention on Psychiatric Nurses’ Knowledge Regarding Ethical and Legal Issues for Psychiatric Patients

Abstract: Background: Nurses' knowledge of legal and ethical aspects of healthcare is essential for all nursing professionals because nurses are expected to be professionally competent, providing high-quality care in an ethical manner.Aim: To assess the effectsof an educational interventionon psychiatric nurses' knowledge regarding legal and ethical issues associated with psychiatric patient treatment. Design:A quasi-experimental, single-group, pre-test-post-test design was used. Setting:Al-Abbasia Mental Health Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…Concerning gender of the studied nurses, the present study showed that more than half were females, from the investigator's point of view, this might be due to the fact that most of the graduates of the nursing profession are females despite the difference in society's view of the profession and the entry of males into the field of nursing work, but the number of workers in the profession remains females more than males. This result is congruent with study by Hussien & Hassona, (2021) [10] entitled "Effect of educational intervention on psychiatric nurses' knowledge regarding ethical and legal issues for psychiatric patients" which showed that more than half of the studied nurses were females. Related to beneficence, the present study showed that the majority of the studied nurses had correct answer regarding known any information about ethics, this result is in disagreement with Ali, et al, (2018) [3] who conducted study about " Professional ethics practiced by nurses working in hemodialysis unit at Zagazig hospitals" and illustrated that three fifth of the studied nurses had low level of knowledge about ethics.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning gender of the studied nurses, the present study showed that more than half were females, from the investigator's point of view, this might be due to the fact that most of the graduates of the nursing profession are females despite the difference in society's view of the profession and the entry of males into the field of nursing work, but the number of workers in the profession remains females more than males. This result is congruent with study by Hussien & Hassona, (2021) [10] entitled "Effect of educational intervention on psychiatric nurses' knowledge regarding ethical and legal issues for psychiatric patients" which showed that more than half of the studied nurses were females. Related to beneficence, the present study showed that the majority of the studied nurses had correct answer regarding known any information about ethics, this result is in disagreement with Ali, et al, (2018) [3] who conducted study about " Professional ethics practiced by nurses working in hemodialysis unit at Zagazig hospitals" and illustrated that three fifth of the studied nurses had low level of knowledge about ethics.…”
Section: Discussionsupporting
confidence: 90%